4(3b-1)=5(2b+3)

Simple and best practice solution for 4(3b-1)=5(2b+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3b-1)=5(2b+3) equation:


Simplifying
4(3b + -1) = 5(2b + 3)

Reorder the terms:
4(-1 + 3b) = 5(2b + 3)
(-1 * 4 + 3b * 4) = 5(2b + 3)
(-4 + 12b) = 5(2b + 3)

Reorder the terms:
-4 + 12b = 5(3 + 2b)
-4 + 12b = (3 * 5 + 2b * 5)
-4 + 12b = (15 + 10b)

Solving
-4 + 12b = 15 + 10b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-10b' to each side of the equation.
-4 + 12b + -10b = 15 + 10b + -10b

Combine like terms: 12b + -10b = 2b
-4 + 2b = 15 + 10b + -10b

Combine like terms: 10b + -10b = 0
-4 + 2b = 15 + 0
-4 + 2b = 15

Add '4' to each side of the equation.
-4 + 4 + 2b = 15 + 4

Combine like terms: -4 + 4 = 0
0 + 2b = 15 + 4
2b = 15 + 4

Combine like terms: 15 + 4 = 19
2b = 19

Divide each side by '2'.
b = 9.5

Simplifying
b = 9.5

See similar equations:

| -76+12x=5x+29 | | 5.5x=0.1(4x+10) | | 7-7y=5 | | 9+7x-4x=12 | | ln(x-3)+ln(3x+1)=6forx | | -3x+3(5x-5)=-147 | | 3+2x-3x=10 | | 35+15x=17x | | fx-gx=hforx | | 3(x+4)+x=(2x-7) | | -2x+2+3x=6 | | 7p-(p+4)=-2(2p-1)+10 | | 3-x+4x=6 | | 5+7x-x=71 | | X+1.5x= | | 7x-7y=5solvey | | 4nsquared+4n-168=0 | | k=gd | | 21x+1=4 | | 6m+6(6m-3)=108 | | 10-5t=6t-23 | | f(x)=ln(e^2x) | | y+3=.5(x-4) | | 16y^8= | | 3x+84=75 | | 72x+9y=18 | | 13x=2(5x+3) | | 9(x+7)+10=11x-2(x-3) | | 24-2x=14x-21 | | 3x^3+8x=420 | | 5b^4=134 | | 5+3(3x-5)=5-4(2x+1) |

Equations solver categories